Preparation of binary nanofluid with heat transfer additives by particle surface functionalisation - Muhammad, Umar Aliyu; Bhattacharyya, Debabrata; Endrino, José L.; Fereres, Sonia (Springer, 2021)
Current binary nanofluid synthesis methods with heat transfer additives lack an understanding of the chemistry of the nanoparticle-additive-base fluid interaction, which plays a significant role in the adsorption of the surfactant on the nanoparticle surface. Consequently, this leads to the formation of aggregates within the nanofluid after a couple of days, affecting the stability of the colloidal suspension. Here, a lithium bromide-alumina salt-based nanofluid is proposed following a newly developed synthesis method including particle surface functionalisation. The new procedure developed allows the initial preparation of the nanoparticles with the surfactant as the first step (surface functionalisation) and then the preparation of the base fluid with a dispersion stabilising agent (Gum Arabic) separately. This is then followed by the dispersion of the prepared alumina nanoparticles into the base fluid, by stirring and ultrasonication to produce the final nanofluid, lithium bromide-water (LiBr-H2O)-alumina nanofluid. Until now, proper procedures have not been reported for the nanofluid synthesis combining surfactant and dispersant and the chemistry of nanoparticles-surfactant-base fluid interaction, which was thoroughly investigated in the new approach. The fluid prepared by both the conventional and new procedures was characterised and analysed simultaneously. A thermal conductivity enhancement of 3% was achieved by using the surface functionalisation method, with greater particle concentration distribution (number of particles in suspension) of 22.7% over the conventional procedure. It also achieved a 5% decrease in dynamic viscosity. On the other hand, a Mouromtseff number value between 0.7 and 1.8 was obtained for the fluid at 293 K and 373 K temperature range, indicating a strong heat transfer capability. It was apparent from the particle size and concentration distribution analysis conducted that this procedure produced a more stable nanofluid with a high distribution of nanoparticles within the fluid. This allows high improvement of thermal properties of the fluid.
Keywords: Heat transfer additives; Dynamic viscosity; LiBr/H2O-Al2O3 nanofluid; Mouromtseff number; Particle distribution; Thermal conductivity